Using the CLOX drawing task to educate the public of the effects of hearing loss - Quinn, Sandra C.M.; Henshaw, Helen; Clark, Daniel; Falck, Claire; Smith, Sandra (Pion, 2010)
We describe a task used to educate the public on the importance of hearing and the experience of hearing loss. During an open day at Nottingham University, participants were presented with verbal instructions (with or without a background masker) and asked to draw the image of a clock face as accurately as possible. Poorest performance was observed when the instructions were presented with a background masker. We suggest that the task could be applied effectively by healthcare professionals who aim to educate younger individuals of the difficulties associated with hearing loss.